Деякі правила визначення предметної юрисдикції адміністративних судів - Гордєєв, Віталій Володимирович; Бзова, Лаура Георгіївна (My University, 2021)
The problem of delimitation of court jurisdiction is a central problem of the Ukrainian judiciary. Not only the plaintiff, but also the courts often make mistakes in determining their own competence to consider and resolve cases, which leads to a violation of the individual’s right to a speedy and fair trial. There are many cases when violation of the rules of jurisdiction is the reason for revocation of a court decision. Jurisdiction of administrative cases is a legal institution that contains a set of legal features (properties) of an administrative case, on the basis of which the law determines the court that has the right and obligation to consider such an administrative case and resolve it on the merits. Observance of the rules of jurisdiction promotes rapid, comprehensive and complete consideration of the administrative case, taking into account its specific features, compliance with the principle of legality and equality of all participants in the administrative process before the law and the court, increases the educational value of justice. The jurisdiction of different courts of the judiciary should be determined depending on the functions they perform, the subject matter, the subjects of the dispute to be considered, and the place (territory) covered by a particular court. Peculiarities in the delimitation of jurisdiction arise if, in determining the criteria for such delimitation, the law is based on various features that are not consistent with each other, as a result of which the same dispute can be formally considered by courts of different jurisdictions. In solving such problems, procedural science and practice, guided by the unwritten dogma of the impossibility of an alternative in determining judicial jurisdiction, devotes all its efforts to resolving alleged conflicts. Дослідження правил про юрисдикцію адміністративних судів сприяє швидкому, всебічному і повному розгляду справи з урахуванням її конкретних особливостей, дотриманням принципу законності та рівності всіх учасників адміністративного процесу перед законом і судом, підвищує виховне значення правосуддя. Особливості в розмежуванні юрисдикції виникають у разі, якщо при визначенні критеріїв такого розмежування закон виходить із різнопланових ознак, не узгоджених між собою, внаслідок яких один і той самий спір формально може бути розглянутий судами різних юрисдикцій. Для правильного визна- чення предметної юрисдикції адміністративних судів необхідно враховувати суб’єктний склад правовідносин, предмет спору, характер спірних матеріальних правовідносин та суть спору.
Keywords: административное дело, юрисдикция, административное судопроизводство, предметная юрисдикция; administrative case, jurisdiction, administrative proceedings, subject jurisdiction